Estimating the effect size of the 15Q11.2 BP1-BP2 deletion and its contribution to neurodevelopmental symptoms: recommendations for practice - Jønch, Aia Elise; Douard, Elise; Moreau, Clara; Van Dijck, Anke; Passeggeri, Marzia; Kooy, Frank; Puechberty, Jacques; Campbell, Carolyn; Sanlaville, Damien; Lefroy, Henrietta; Richetin, Sonia; Pain, Aurelie; et al. (Journal of Medical Genetics, 2019)
Background: The 15q11.2 deletion is frequently identified in the neurodevelopmental clinic. Case-control studies have associated the 15q11.2 deletion with neurodevelopmental disorders, and clinical case series have attempted to delineate a microdeletion syndrome with considerable phenotypic variability. The literature on this deletion is extensive and confusing, which is a challenge for genetic counselling. The aim of this study was to estimate the effect size of the 15q11.2 deletion and quantify its contribution to neurodevelopmental disorders. Methods: We performed meta-analyses on new and previously published case-control studies and used statistical models trained in unselected populations with cognitive assessments. We used new (n=241) and previously published (n=150) data from a clinically referred group of deletion carriers. 15q11.2 duplications (new n=179 and previously published n=35) were used as a neutral control variant. Results: The deletion decreases IQ by 4.3 points. The estimated ORs and respective frequencies in deletion carriers for intellectual disabilities, schizophrenia and epilepsy are 1.7 (3.4%), 1.5 (2%) and 3.1 (2.1%), respectively. There is no increased risk for heart malformations and autism. In the clinically referred group, the frequency and nature of symptoms in deletions are not different from those observed in carriers of the 15q11.2 duplication suggesting that most of the reported symptoms are due to ascertainment bias. Conclusions: We recommend that the deletion should be classified as € pathogenic of mild effect size'. Since it explains only a small proportion of the phenotypic variance in carriers, it is not worth discussing in the developmental clinic or in a prenatal setting.
CRIS-Team Scopus Importer:2019-09-27
Keywords: 15q11.2 copy-number variants; congenital heart disease; epilepsy; loss-of-function intolerance; neurodevelopmental disorders